Aquatic invertebrate community structure of selected endorheic wetlands (pans) in South Africa. Issue 3 (1st January 2016) - de Necker, L.; Ferreira, M.; van Vuren, J.H.J.; Malherbe, W.
Abstract: Shallow wetlands, such as pans, are not well studied in South Africa, even though they perform many important functions, such as providing an important food source for migratory birds and habitat to highly specialized fauna. Aquatic invertebrate diversity, abundance, and water quality in pans were analysed seasonally from 3 provinces in South Africa with contrasting climates. Univariate and multivariate statistics were used to assess similarities in aquatic invertebrate communities and water chemistry among pans. Pans inundated for extended periods had greater aquatic invertebrate diversity, and several of these taxa were not adapted to the temporary environment common to pans. The subtropical region had greater aquatic macroinvertebrate diversity than semiarid regions due to more rainfall per annum in the subtropical region. Water temperature was a major driving factor for diversity, with greater diversity occurring in warmer seasons. High water hardness and salinity were found to drive decreased diversity and encourage the presence of hardy and more tolerant species. Understanding the importance of these aforementioned factors (i.e., pan longevity, temperature, water hardness, and salinity) influencing aquatic invertebrate biodiversity in pans provides a baseline for future studies and impact assessments on these important and understudied systems.